Platelet Contributions to Myocardial Ischemia/Reperfusion Injury - Schanze, Nancy; Bode, Christoph; Duerschmied, Daniel (Frontiers in Immunology, 2019)
Myocardial infarction causes ischemia of the heart tissue downstream of the occluded vessel. Prolonged oxygen deficiency provokes tissue necrosis, which can lead to heart failure and death of the patient. Therefore, restoration of coronary blood flow (reperfusion of the ischemic area) by re-canalizing the affected vessel is essential for a better patient outcome. Paradoxically, sudden reperfusion also causes tissue injury, thereby increasing the initial ischemic damage despite restoration of blood flow (= ischemia/reperfusion injury, IRI). Myocardial IRI is a complex event that involves various harmful mechanisms (e.g. production of reactive oxygen species and local increase in calcium ions) as well as inflammatory cells and signals like chemokines and cytokines. An involvement of platelets in the inflammatory reaction associated with IRI was discovered several years ago, but the underlying mechanisms are not yet fully understood. This mini review focusses on platelet contributions to the intricate picture of myocardial IRI. We summarize how upregulation of platelet surface receptors and release of immunomodulatory mediators lead to aggravation of myocardial IRI and subsequent cardiac damage by different mechanisms such as recruitment and activation of immune cells or modification of the cardiac vascular endothelium. In addition, evidence for cardioprotective roles of distinct platelet factors during IRI will be discussed.